Antibiotic resistance in Vibrio spp isolated from shrimp Litopenaeus vannamei. Treatment alternatives with extracts of neem (Azadirachta indica) and oregano (Origanum vulgare) - Aguirre Chanta, Luis E. (2021)
The study aimed to characterize the antibiotic resistance in Vibrio spp isolated from Litopenaeus vannamei and to test oregano (Origanum vulgare) and neem (Azadirachta indica) extracts for their inhibition. Farmed shrimp were collected in Santa Rosa (Ecuador) and samples of hepatopancreas, hemolymph and lesions were taken. Fourteen strains of Vibrio spp were isolated. Another 14 strains of Vibrio spp isolated from farmed shrimp from Tumbes (Peru) were obtained through a donation. The antibiotic resistance of the strains against 10 antibiotics and the sensitivity of four of them (two resistant and two multi-resistant to antibiotics) were evaluated using neem and oregano aqueous extracts (EA), ethanolic (EE), as well as purified with soxhlet and rota evaporator (EPSR). The 28 strains studied were resistant to at least one of the antibiotics, 64.3% were multi-resistant and 50% were resistant to oxytetracycline. Neem and oregano EA and EE did not inhibit any of the four strains, but the undiluted neem EPSR inhibited one of the four strains tested, showing a greater inhibitory effect even than oxytetracycline in it. Undiluted oregano EPSR inhibited all four strains tested. It is concluded that there is high antibiotic resistance in Vibrio spp isolated from farmed shrimp in Santa Rosa and Tumbes; that the EPSR of oregano is an interesting alternative to inhibit Vibrio spp resistant to antibiotics, as well as that the EPSR of neem could be used to inhibit some strains of Vibrio spp resistant to oxytetracycline.